Prognostic impact of cytogenetic abnormalities detected by FISH in AL amyloidosis with daratumumab-based frontline therapy - Chakraborty, Rajshekhar; Zanwar, Saurabh; Hegenbart, Ute; Bhutani, Divaya; Gertz, Morie A.; Dispenzieri, Angela; Kumar, Shaji; D'Souza, Anita; Patwari, Anannya; Cowan, Andrew; Chen, Guizhen; Milani, Paolo; et al. (Blood, 2024)
We performed an international retrospective study on 283 patients with light chain (AL) amyloidosis to investigate the prognostic impact of cytogenetic abnormalities by fluorescence in situ hybridization, when treated with frontline daratumumab-based therapy. The cytogenetic subgroups of interest were t(11;14), gain/amp(1q) (hereafter, +1q), hyperdiploidy, deletion(13q), del(17p), and myeloma high-risk (HR) translocations (t[4;14], t[14;16], or t [14;20]). The end points of interest were rate of hematologic complete response (heme-CR), very good partial response (VGPR) or better, and hematologic event-free survival (heme-EFS). The incidence of abnormalities was as follows: t(11;14), 53.4%; deletion (13q), 28.9%; +1q, 22.3%; hyperdiploidy, 19.4%; HR translocations, 6.6%; and deletion(17p), 4.5%. The heme-CR rate by cytogenetic subgroups were as follows: t(11;14) vs no t(11;14), 45.2% vs 41.8% (P=0.597); del(13q) vs no del(13q), 46.8% vs 42.8% (P=0.594); +1q vs no +1q, 30.2% vs 47.9% (P=0.022); hyperdiploidy vs no hyperdiploidy, 39.5% vs 44.9% (P=0.541); HR translocations vs none, 45.5% vs 43.1% (P=0.877); and del(17p) vs no del(17p), 50.0% vs 42.9% (P=0.658), respectively. Similarly, +1q was the only subgroup with a significantly lower VGPR or better rate (64.2% vs 79.0%; P=0.033). At a median follow-up of 19.8 months, the median heme-EFS was 49.6 months (95% CI, 24.7-not reached [NR]), and the 2-year overall survival (OS) was 80.98% (95% CI, 75.6-85.4). The presence of +1q was significantly associated with worse heme-EFS on multivariate analysis (HR 2.06,95% CI, 1.14-3.71; P=0.017). Notably, there was no adverse prognostic impact of t(11;14) on heme-EFS or OS. In conclusion, +1q is associated with worse outcome in the daratumumab-era. Clinical trials testing novel frontline immunotherapies should be enriched in +1q to further improve outcomes in this subgroup.
Gesehen am 03.12.2025
Online verfügbar: 30. August 2024, Artikelversion: 19. Dezember 2024